Genetic diversity and antigenic variations of porcine circovirus type 2 genotypes in Brazilian swine herds: Implications for vaccine efficacy and viral evolution - H.I.J. Nascimento; J.L.R. Cunha; A.L.S. Fraiha; B.S.A.S. Santos; B.M.M. Rocha; N.R. Aguilar; B.F.S. Ribeiro; D.C. Veit; K.A. Franz; É.G. Franco; V.L.A. Fernandes; D.P. Três; et al. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2025)
ABSTRACT Between 2019 and 2021, 106 clinical samples from pigs showing signs compatible with diseases associated with Porcine Circovirus (PCVD) were collected from various regions in Brazil, including the South, Southeast, and Central-West. The animals were sourced from commercial pig farms and had been previously vaccinated against PCV2. The collected samples were genotyped for PCV2, and the sequences were subsequently analyzed. The predominant genotype found was PCV2d (75.47%), followed by PCV2b (22.64%), while PCV2a was not detected. The sequences of PCV2b and PCV2d obtained were highly conserved within their respective genotypes but showed significant differences in antigenic sites, which may affect pathogenicity and/or antigenicity. When comparing PCV2d sequences with ORF2 amino acid sequences from three commercial vaccines used in Brazil (one containing PCV2b and two containing PCV2a), most amino acid residues in epitope regions were conserved, suggesting good cross-reactivity between vaccines and PCV2d. However, mutations were detected in residues essential for viral neutralization, which may impact vaccine efficacy. Further studies are needed to better understand these mutations and strengthen genotype surveillance of PCV2 in Brazil.